Bidding on the dream contract : does Rahul have a business strategy? - Thomas, Nobin (London : SAGE Publications: SAGE Business Cases Originals, 2022)
The case describes Rahul's entrepreneurial journey, from building his product design skills to launching his own tech business and landing a successful subcontract with an oceanography company. Faced with the chance to bid directly on a large contract for submarine technology, he is having doubts. Rahul decided to pursue his dream after completing his higher education and gaining foundational work experience. He founded the firm ATWIC R&D, which specializes in core electronics, communications, and instrumentation-based sensor networks. Rahul and his small team at ATWIC are skilled in many areas, but they have failed to develop a solid business strategy and, like many technical founders, Rahul's technical expertise often overshadows his insight into business decisions. The case also illustrates the tensions between an entrepreneur's quest for excellence and the day-to-day requirements of operating a firm.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Entrepreneurship -- Case studies; Business planning -- Case studies